Antidepressant discontinuation syndrome-a case report - Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Abang Abdullah, Khadijah Hassanah; Abdul Manap, Abdul Hadi (University of Malta, 2021)
Antidepressant discontinuation syndrome (ADDS) is often an under-recognised cause of multiple unpleasant symptoms upon stopping antidepressant. It requires a high index of suspicion to not miss this elusive diagnosis. This case will look at a common scenario of a nursing home resident forgetting to refill his antidepressant prescription which lead to the above syndrome. This will lead to discussion on how to treat this syndrome and subsequently allow the patient to carry on their daily life.